Targeted haplotyping in pharmacogenomics using Oxford Nanopore Technologies’ adaptive sampling - Deserranno, Koen; Tilleman, Laurentijn; Rubben, Kaat; Deforce, Dieter; Van Nieuwerburgh, Filip (Frontiers in Pharmacology, 2023)
Pharmacogenomics (PGx) studies the impact of interindividual genomic variation on drug response, allowing the opportunity to tailor the dosing regimen for each patient. Current targeted PGx testing platforms are mainly based on microarray, PCR, or short-read sequencing. Despite demonstrating great value for the identification of single nucleotide variants (SNVs) and insertion/deletions (INDELs), these assays do not permit identification of large structural variants, nor do they allow unambiguous haplotype phasing for star-allele assignment. Here, we used Oxford Nanopore Technologies' adaptive sampling to enrich a panel of 1036 genes with well-documented PGx relevance extracted from the Pharmacogenomics Knowledge Base (PharmGKB). By evaluating concordance with existing truth sets, we demonstrate accurate variant and star-allele calling for five Genome in a Bottle reference samples. We show that up to three samples can be multiplexed on one PromethION flow cell without a significant drop in variant calling performance, resulting in 99.35 % and 99.84 % recall and precision for the targeted variants, respectively. This work advances the use of nanopore sequencing in clinical PGx settings.